Georadar, georradar, georrádar… New patterns for the classification of Spanish neological formal variation - Sánchez Ibáñez, Miguel (Círculo de Lingüística Aplicada a la Comunicación, 2022)
Formal variation is one of the main features that help us define what a neologism is. New words go through an initial stage of formal instability, before becoming total members of the languages they are inserted into. Basing our study on more than 6,000 neologisms compiled in the press along the past eight years, we have observed and classified the main trends of formal variation in current Spanish neologisms. For that purpose, a scoring scale has been designed, which favours the formally stable neologisms and not the unstable ones. The scale takes into account the absolute frequency of each unit in the corpus, the number of variants addressing the same concept, and the difference in absolute frequency among them. Results prove the existence of new relevant kinds of formal variation, such as the alternation between joining and separating lexical elements by means of hyphens, or the attempts to adapt the new units to the orthographical rules. Likewise, the prevailing trends within each kind of formal variation detected have been defined.